Implikasi Perubahan Lingkungan Bisnis terhadap Strategi Perusahaan, Studi Kasus: PT Bogasari Flour Mills - Suwarsono Muhammad; Andi Yuliansyah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This study discussed the emergence of business on PT Bogasari Flour mills before and after economic crisis 1997/1998 in Indonesia. Based on SWOT analysis with regard to business environment and governement policy, the study was able to identify prospected flour mills market. The results of the analysis indicate that government policy affected the implemented strategy of PT. Bogasari Flour MillsKeyword: maklun, environmental, brand, strategy